Workshop on Improving the Quality of Nursing Services for Post-SC Patients Using JKN-PBI at Grandmed Hospital, Lubuk Pakam (JURNAL PENGMAS KESTRA (JPK), 2025)
The increasing number of Caesarean Section (CS) deliveries in hospitals demands high-quality, safe, and patient-centered post-operative care. In the context of the National Health Insurance system, patients receiving Premium Assistance (JKN-PBI) are a vulnerable group to disparities in service quality, including in post-CS nursing care. Nurses play a strategic role in ensuring the quality of nursing care for post-CS patients through the implementation of service standards, patient safety, and empathetic and equitable therapeutic communication. Therefore, improving nurses' competence and understanding is crucial in efforts to improve the quality of hospital services. This community service activity aims to increase nurses' knowledge regarding the quality of nursing care for post-CS patients using JKN-PBI at Grandmed Hospital Lubuk Pakam. The method used was a participatory workshop with an educational and applied approach. The activity was carried out through preparation, implementation, and evaluation stages, involving nurses in the inpatient obstetrics and post-operative care wards. The results of the activity showed an increase in nurses' knowledge after attending the workshop. The proportion of participants with good knowledge increased from 30.0% in the pre-test to 80.0% in the post-test, while those with poor knowledge decreased to 0%. The workshop was effective in increasing nurses' understanding of post-cesarean nursing care standards, patient safety, and equitable nursing services for JKN-PBI patients. It was concluded that the workshop on improving the quality of nursing services contributed positively to increasing nurse capacity and has the potential to improve the quality of nursing services for post-cesarean patients using JKN-PBI. This activity is recommended for ongoing implementation as part of the hospital's quality improvement and human resource development strategy.